Happy Anniversary UMPSA - Noraisah Nurul Fatwa, Mohd Razali (UMPSA, 2024)
In the heart of Pahang's embrace, A beacon of knowledge, grace, From KUKTEM to UMP, a journey so great, And now UMPSA, twenty-two years we celebrate